Specific accumulation of technetium-99m radiolabelled, negative liposomes in the inflamed paws of rats with adjuvant induced arthritis: effect of liposome size. - Love, W G (1989)
Technetium-99m labelled, negatively charged liposomes accumulate in the inflamed tissue of rats with adjuvant induced arthritis. Up to 10 times more liposome accumulation was seen in inflamed paws than in paws of control rats, and this represented 5.3% of the injected liposome dose. The accumulation of liposomes in inflamed tissue was directly related to the liposome size, the maximal accumulation occurring with liposomes less than 100 nm in diameter.